The regulatory function of Blastocystis spp. on the immune inflammatory response in the gut microbiome - Rojas-Velázquez, Liliana; Morán, Patricia; Serrano-Vázquez, Angélica; Portillo-Bobadilla, Tobías; González, Enrique; Pérez-Juárez, Horacio; Hernández, Eric; Partida-Rodríguez, Oswaldo; Nieves-Ramírez, Miriam; Padilla, Angeles; Zaragoza, Martha; Ximénez, Cecilia (Frontiers in Cellular and Infection Microbiology, 2022)
Blastocystis spp. is a unicellular organism that inhabit the digestive tract of various vertebrates, with a worldwide distribution and a variable prevalence. For many years Blastocystis spp. was considered a cyst of a flagellate, a fungus, or a saprophyte yeast of the digestive tract, in 1996 it is placed in the group of stramenopiles (heterokonts). Since its new classification, many questions have arisen around this protist about its role as a pathogen or non-pathogen organism. Recent evidence indicates that Blastocystis spp. plays a role in the immune inflammatory response in the gut microbiome generating an anti-inflammatory scenario, characterized by a lower concentration of fecal inflammatory markers in infected human hosts. Here, we review recent findings on the regulatory function of Blastocystis spp. in the immune inflammatory response to better understand the role of Blastocystis spp. in health and disease, clarifying whether Blastocystis spp. is truly a pathogen, a commensal or even a mutualist in the human gut microbiome.